Why the EU Supports the Food Security Portal - Thomas, Phillippe (2020)
Phillippe Thomas POLICY SEMINAR Virtual Event - Information Needs for Food Crisis Risk Early Warning: The Role of the Food Security Portal Co-Organized by IFPRI and the Food Security Portal (FSP) NOV 24, 2020 - 09:30 AM TO 11:00 AM EST